ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL SERTA DAMPAK STRUKTUR MODAL TERHADAP RETURN SAHAM PERUSAHAAN FOOD AND BEVERAGE DI BEI - Moh. Nakib; Roni Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to determine the factors that influence capital structure and the impact of capital structure on stock returns in food and beverage companies listed on Indonesian Stock Exchange. The populations of this research were 18 food and beverage companies listed on the Stock Exchange during 2015-2017. With purposive sampling method obtained a sample of 14 food and beverage companies. This study uses secondary data and path analysis methods. The independent variables used are growth of asset, firm size, profitability, and business risk. The results of the study explain that growth of asset, firm size, profitability have a positive and significant effect on capital structure (DER), while business risk has a negative and significant effect on capital structure (DER). Other findings from this study are that the capital structure (DER) has a positive and significant effect on stock returns. Keywords: stock return, DER, growth of asset, firm size, profitability and business risk